2022
DOI: 10.1016/j.ultsonch.2021.105886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on the kinetics of anti-solvent crystallization of sucrose

Abstract: Highlights Investigated anti-solvent crystallization of sucrose. Measurement of supersaturation level of anti-solvent crystallization. Abegg Stevens and Larson model was used to calculate crystallization kinetics. Lower activation energy of crystallization in an ultrasonic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The authors hypothesize that lower ultrasonic energies destroy the formation of subnuclei in solution, while higher ultrasonic energies increase intermolecular collisions and promote the agglomeration of these clusters beyond the critical nucleation radius. Zhong et al 98 studied the effect of ultrasound on the kinetics of sucrose antisolvent crystallization, and the results showed that when the ultrasound power is <72 W, the cavitation effect makes the nucleation play a dominant role. When the ultrasonic power is >72 W, the researchers believe that it may be due to the high viscosity of sucrose, which weakens the cavitation effect, thereby reducing the nucleation rate, increasing the growth rate, and obtaining crystals with larger particle sizes.…”
Section: Physical Fields To Inhibitmentioning
confidence: 99%
“…The authors hypothesize that lower ultrasonic energies destroy the formation of subnuclei in solution, while higher ultrasonic energies increase intermolecular collisions and promote the agglomeration of these clusters beyond the critical nucleation radius. Zhong et al 98 studied the effect of ultrasound on the kinetics of sucrose antisolvent crystallization, and the results showed that when the ultrasound power is <72 W, the cavitation effect makes the nucleation play a dominant role. When the ultrasonic power is >72 W, the researchers believe that it may be due to the high viscosity of sucrose, which weakens the cavitation effect, thereby reducing the nucleation rate, increasing the growth rate, and obtaining crystals with larger particle sizes.…”
Section: Physical Fields To Inhibitmentioning
confidence: 99%
“…This is because the local high temperature induced by ultrasound increased the probability of particle redissolution and then recrystallization growth on the existing crystals. Furthermore, in sucrose anti-solvent crystallization, Zhong et al 59 found that the ultrasonic field did not affect the shape of the sucrose crystal, whereas it affected the particle size. Further exploration showed that when the ultrasonic power was lower than 72 W, nucleation played a dominant role owing to the cavitation effect.…”
Section: Intensification Of Crystal Growthmentioning
confidence: 99%
“…Numerous studies have reported beneficial results with the assistance of ultrasound in the crystallization process. Ultrasound can promote nucleation, 15 narrow particle size distribution, 16,17 decrease agglomeration, 18 control polymorphs, and accelerate polymorphic transformation. [19][20][21] The benefits that can be obtained by the application of ultrasound in crystallization depend on different operating parameters such as the frequency of irradiation, power dissipation, time of ultrasound application, and the type of reactor.…”
Section: Introductionmentioning
confidence: 99%